Advances in Corticosteroid Therapy for Ocular Inflammation: Loteprednol Etabonate - Timothy L. Comstock; Heleen H. DeCory (International Journal of Inflammation)
Topical corticosteroids are effective in reducing anterior segment inflammation but are associated with adverse drug reactions (ADRs) including elevation of intraocular pressure (IOP) and cataract formation. Retrometabolic drug design has advanced the development of new corticosteroids with improved therapeutic indices. Engineered from prednisolone, loteprednol etabonate (LE) has a 17α-chloromethyl ester, in lieu of a ketone group, and a 17β-etabonate group. LE is highly lipophilic and binds with high affinity to the glucocorticoid receptor; any unbound LE is metabolized to inactive metabolites. LE has been studied in several anterior segment inflammatory conditions (giant papillary conjunctivitis, allergic conjunctivitis, anterior uveitis, and keratoconjunctivitis sicca), and in postoperative ocular inflammation and pain. Combined with tobramycin, it is effective in blepharokeratoconjunctivitis. Elevations in IOP are infrequent with LE, and the absence of a C-20 ketone precludes formation of Schiff base intermediates with lens proteins, a common first step implicated in cataract formation with ketone steroids.